Examining Self-Compassion, Social Support, And Mental Well-Being Among Fast Track Students at UIN Malang - Ahyani, Shidqi; Arifa, Laily Nur; Sari, Sulistya Umie Ruhmana; Kadarisman, Ali (Al Ulya: Jurnal Pendidikan Islam, 2024)
This study explores the relationship between self-compassion, perceived social support, academic stress, and mental well-being among Fast Track students at UIN Malang. Adopting a quantitative approach, the research employs a correlational design to examine the interactions of these variables in a high-pressure academic environment. Data were collected from a 61% sample of Fast Track students using a structured questionnaire, incorporating validated scales for self-compassion, social support, academic stress, and mental well-being.  The findings reveal that Fast Track students generally exhibit high self-compassion, significantly correlated with their mental well-being. High levels of self-kindness, mindfulness, and an awareness of shared humanity were prominent among the students, suggesting a solid psychological resilience. Perceived social support from family and friends significantly impacted overall well-being, though its direct influence on academic stress was more complex. The research did not find a significant direct relationship between self-compassion and academic stress, indicating that self-compassion aids in managing emotional responses to stress rather than reducing it.The study underscores the need for a holistic approach to supporting students in accelerated academic programs. The findings suggest that enhancing self-compassion and strengthening social support networks can improve students' academic performance and mental well-being. This research contributes to understanding students' psychological dynamics in high-pressure academic settings. It provides insights for developing targeted interventions and support systems to foster a balanced and supportive educational environment.